2023
DOI: 10.1186/s12885-023-10854-x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Osteopontin splice variants in cancer

Abstract: Background The cytokine Osteopontin is a mediator of tumor progression and cancer metastasis. In 2006, we reported that (in addition to the full-length form -a) splice variants of Osteopontin (forms -b and -c) are produced selectively by transformed cells. Through June 2021, 36 PubMed-indexed journal articles have studied Osteopontin splice variants in various cancer patients. Methods Applying a categorical approach previously developed by us, here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…A recent comprehensive meta‐analysis of studies on OPN variants highlighted the association of specific splice variants with tumor grade, stage, or patient survival in various cancers. 11 However, in the case of MM, the only available study to date is our previous investigation focusing on five OPN splice variants ( OPNa , OPNb , OPNc , OPN4 , and OPN5 ) and their correlation with clinicopathological features of patients’ tumor tissues. 16 The present study aimed to analyze the relative gene expression levels of OPN isoforms in cell lines derived from primary and MM tissues and explore the association with clinicopathological parameters and invasive capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comprehensive meta‐analysis of studies on OPN variants highlighted the association of specific splice variants with tumor grade, stage, or patient survival in various cancers. 11 However, in the case of MM, the only available study to date is our previous investigation focusing on five OPN splice variants ( OPNa , OPNb , OPNc , OPN4 , and OPN5 ) and their correlation with clinicopathological features of patients’ tumor tissues. 16 The present study aimed to analyze the relative gene expression levels of OPN isoforms in cell lines derived from primary and MM tissues and explore the association with clinicopathological parameters and invasive capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these variants, four additional isoforms have been described for OPN5 (OPN5b, OPN5c, OPN5d, and OPN5e). 10 , 11 , 12 Exons 6 and 7 encode over 80% of the OPN protein, which contains the region responsible for interacting with integrin receptors. Integrins are cell‐surface transmembrane heterodimer receptors, which are formed through noncovalent binding of an α and a β subunits, of which there are 18 and eight variants, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Circumstantial support comes from the observation of total OPN (4 studies, 172 patients [18]) or OPN-c (3 studies, 45 patients [19]) in the progression of premalignant lesions, and from increasing OPN-c blood levels with DCIS progression (67 patients [20]). Currently available tests are described for their basis, their purpose, and the target population they serve.…”
Section: Table 1: Opn Splice Specificity and Sensitivity In Premalign...mentioning
confidence: 99%
“…The different splice variants including osteopontin-a, -b, and -c, are expressed differentially in cancers [ 40 , 41 ]. A meta-analysis based on data in published literature supplemented with data from the TSVdb concluded that in lung cancer, OPN-a, OPN-b, and OPN-c were increased in comparison to normal tissue, while in breast cancer, OPN-c was elevated [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The different splice variants including osteopontin-a, -b, and -c, are expressed differentially in cancers [40,41]. A meta-analysis based on data in published literature supplemented with data from the TSVdb concluded that in lung cancer, OPN-a, OPN-b, and OPN-c were increased in comparison to normal tissue, while in breast cancer, OPN-c was elevated [42]. Within the region encoded by exons 6 and 7 is a conserved Arg-Gly-Asp (RGD) sequence that interacts with αvb1, αvb3, and αvb5 integrins, allowing binding to various components of the extracellular matrix as well as some cell types.…”
Section: Introductionmentioning
confidence: 99%